Plasma Characteristics of Under-water Arc Discharge in Nanoparticle Fabrication - Athaya Cantia Putri; Miftahul Anwar; Irwan Iftadi; Agus Ramelan; Feri Adrianto; Teguh Endah Saraswati (Journal of Electrical, Electronic, Information, and Communication Technology, 2022)
Synthetic nanoparticles are the process of making particles with a size of less than 100 nm and changing the properties of the material so that it can be improved to improve the usability of new products. One method that can be used is the arc discharge method in water, which is a synthetic method of nanoparticles, which is very simple because it does not require complicated equipment. This study uses graphene as an electrode, which is then immersed in water and mounted horizontally. Current and voltage monitoring is carried out during the arc discharge process using a Hall-based current sensor and the voltage is measured directly between the two electrodes. Variations in input current of 10A, 40A, 70A, and 100A affect the arc formed, current and voltage, and ionization energy. Monitoring with OES is also carried out to determine the shape of the plasma, and the wavelength when the arc occurs. The results obtained that the current has more effective and optimal results in synthesizing nanoparticles.